Improving depth in phosphoproteomics by using a strong cation exchange-weak anion exchange-reversed phase multidimensional separation approach. - Hennrich, M; Groenewold, V; Kops, G; Heck, A; Mohammed, S (2011)
Several enrichment and separation strategies are available that allow nearly pure phosphopeptide pools to be created. These phosphopeptide pools are too complex to be completely unraveled by RP-LC-MS analysis alone. Here, we implement weak anion exchange (WAX) chromatography as an additional, complementary dimension to strong cation exchange (SCX) and reversed phase (RP). Initially, we used SCX to fractionate a human lysate digest to generate a fraction highly enriched for phosphopeptides. Analysis of this single fraction by RP-LC-MS with a 140 min gradient method allowed the identification of 4045 unique phosphopeptides (false discovery rate (FDR) < 1%; Mascot score > 20) using an Orbitrap Velos. Triplicate analysis (420 min total gradient time) of the same sample increased the total to just over 5000 unique phosphopeptides. When we separated the same sample by WAX and analyzed 14 WAX fractions by 30 min gradient RP-LC-MS (420 min total gradient time) we were able to identify 7251 unique phosphopeptides, an approximate increase of 40%, while maintaining the same total gradient time. We performed a more comprehensive, albeit also more time-consuming, analysis of the same 14 WAX fractions by the use of 140 min gradient LC-MS analyses, which resulted in the detection of over 11 000 unique phosphopeptides. Our results clearly demonstrate that additional separation dimensions are still necessary for in-depth phosphoproteomics and that WAX is a suitable dimension to be combined and sandwiched between SCX and RP chromatography.